The Gating Mechanism of Mechanosensitive Channels in Droplet Interface Bilayers. Issue 1722 (16th June 2015) - Najem, Joseph S.; Freeman, Eric; Sukharev, Sergei; Leo, Donald J.
ABSTRACT: MscL, a large-conductance mechanosensitive channel, is a ubiquitous osmolyte release valve that aids bacteria in surviving abrupt hypo-osmotic shocks. The large scale of its tension-driven opening transition makes it a strong candidate to serve as a transducer in novel stimuli-responsive biomolecular materials. In the previous work, a low-threshold gain-of-function V23T mutant of MscL produced a reliable activation behavior in a droplet interface bilayer (DIB) with applied axial droplet compression. Near the maximal compression, the aqueous droplets deform and the resulting increase in surface area leads to an increase in tension in the water-lipid-oil interface. This increase in tension is the product of the relative change in the droplet surface area and the elastic modulus of the DPhPC lipid monolayer (∼120 mN/m). This paper, presents a study of the physical processes that cause MscL gating in the DIB. Analysis of video during compression and relaxation of the droplets is utilized to estimate the change in the surface area of the droplet and the variation on monolayer surface tension. The monolayer surface tension is proportional to the area change of the droplet normalized to the original surface area. The results demonstrate that the area change in the droplet is negligible at frequencies above 1 Hz, but is approximately 2% at frequencies in the range of 100 mHz. In addition, at low frequencies (∼0.2 Hz) bilayer thinning occurs at maximum compression, proving an increase in bilayer tension. However, this study also shows that gating at frequencies higher than 0.2 Hz could be achieved through the application of high duty cycle oscillation (∼75%). The relative change in monolayer area increases significantly at higher duty cycle oscillations where the compression stroke is much faster than the relaxation stroke.